2024
DOI: 10.1007/s10162-024-00939-0
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus: Clinical Insights in Its Pathophysiology-A Perspective

Berthold Langguth,
Dirk de Ridder,
Winfried Schlee
et al.

Abstract: Tinnitus, the perception of sound without a corresponding external sound source, and tinnitus disorder, which is tinnitus with associated suffering, present a multifaceted clinical challenge due to its heterogeneity and its incompletely understood pathophysiology and especially due to the limited therapeutic options. In this narrative review, we give an overview on various clinical aspects of tinnitus including its heterogeneity, contributing factors, comorbidities and therapeutic pathways with a specific emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Starting from the evidence showing that many clinical aspects of tinnitus are still enigmatic and cannot be fully explained by current models [ 144 ], this study identified significant associations between psychological factors, EEG beta activity, and audiological variables in tinnitus patients.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the evidence showing that many clinical aspects of tinnitus are still enigmatic and cannot be fully explained by current models [ 144 ], this study identified significant associations between psychological factors, EEG beta activity, and audiological variables in tinnitus patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although tinnitus is often of mild impact, its consequences can be devastating. Tinnitus can lead to depression and anxiety, sleep deprivation, and may severely hinder the ability to participate in social activities or work [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%